ANALISIS PERAMALAN (FORCASTING) PENJUALAN DENGAN MENGGUNAKAN WEIGHTED MOVING AVERAGE PADA INDOMARET GRAND TAMAN ROYAL TANGERANG - Suwanda Aditya Saputra (Kurawal - Jurnal Teknologi, Informasi dan Industri, 2026)
Sales forecasting is a crucial aspect of retail management to prevent overstocking or understocking, which can impact customer satisfaction and operational efficiency. This study aims to analyze and measure the accuracy of the Weighted Moving Average (WMA) method in forecasting the sales of five main products at Indomaret Grand Taman Royal Tangerang, namely Chitato, Aqua 600 ml, 5 kg Rice, 5 kg Lifebuoy, and Djarum Super. The WMA method is selected because it gives greater weight to more recent historical data, resulting in predictions that are more responsive to market trend changes. The study uses monthly sales data from the past six periods and a WMA weight ratio of 3:2:1. The forecasting results show high accuracy, with the Mean Absolute Percentage Error (MAPE) values as follows: Chitato 6.28%, Aqua 600 ml 4.51%, 5 kg Rice 7.12%, 5 kg Lifebuoy 5.89%, and Djarum Super 6.03%. The overall average MAPE is 5.97%, indicating very good forecasting accuracy. These findings suggest that the WMA method is effective for sales forecasting and can serve as a decision-making foundation for inventory management and retail sales strategies.